Plasma-surface interaction and mechanisms of dust production in ITER ELM simulation experiments with QSPA Kh-50 - Makhlaj, V.A.; Garkusha, I.E.; Aksenov, N.N.; Byrka, O.V.; Landman, I.; Lebedev, S.I.; Shevchuk, P.B. (Вопросы атомной науки и техники, 2012)
Experimental simulations of ITER transient events with relevant surface heat load parameters (energy density and the pulse duration) were carried out with a quasi-stationary plasma accelerator QSPA Kh-50. The several mechanisms of dust generation from tungsten surfaces were identified. The major cracks development and it bifurcation led to generation dust particles with sizes up to tens μm. Melting of surface and development of fine meshes of cracks along the grain boundaries are accompanied by resolidified bridges formation through the fine cracks. Such bridges produce nm-size dust. Appearance of sub-micron and nanometer-size cellular structures under plasma irradiation can leads to the intensification of the dust formation.